2019
DOI: 10.1002/ppul.24542
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital management of pediatric asthma patients in a large emergency medical services system

Abstract: BackgroundAsthma is a common pediatric diagnosis for emergency medical services (EMS) transports, however there is a paucity of data on prehospital asthma management. The purpose of this study was to describe prehospital management of pediatric patients with suspected asthma exacerbation.MethodsWe conducted a retrospective review of electronic medical records from 24 ground EMS agencies in Southwestern Pennsylvania between 1 January 2014 to 31 December 2017. We identified patients 2 to 17 years with documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Studies performed in Pennsylvania, Florida, and New Mexico each suggest a low rate of administration of intravenous steroids in prehospital encounters for pediatric patients with asthma exacerbations. 5,8,9 In one pilot study, a change in prehospital protocols to include oral dexamethasone administration paired with training increased glucocorticoid administration to asthmatic pediatric patients, with a decrease in hospital admission rate and length of stay. 10 Several studies have demonstrated that dexamethasone and methylprednisolone carry similar efficacy for asthma, 17 and a systematic review of randomized controlled trials identified that oral steroid therapy is particularly effective in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies performed in Pennsylvania, Florida, and New Mexico each suggest a low rate of administration of intravenous steroids in prehospital encounters for pediatric patients with asthma exacerbations. 5,8,9 In one pilot study, a change in prehospital protocols to include oral dexamethasone administration paired with training increased glucocorticoid administration to asthmatic pediatric patients, with a decrease in hospital admission rate and length of stay. 10 Several studies have demonstrated that dexamethasone and methylprednisolone carry similar efficacy for asthma, 17 and a systematic review of randomized controlled trials identified that oral steroid therapy is particularly effective in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials have demonstrated that earlier use of steroids in patients with asthma significantly reduces symptoms and the need for hospital admission, especially in patients with severe asthma 16 However, even in states where steroid use was permissible, their rate of use in pediatric patients is low. Studies performed in Pennsylvania, Florida, and New Mexico each suggest a low rate of administration of intravenous steroids in prehospital encounters for pediatric patients with asthma exacerbations 5,8,9 . In one pilot study, a change in prehospital protocols to include oral dexamethasone administration paired with training increased glucocorticoid administration to asthmatic pediatric patients, with a decrease in hospital admission rate and length of stay 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of EMS in the care of children with acute asthma has been examined in terms of demographics, treatments initiated, and impact on ED stays. [7][8][9] However, similar insights for adults are not known.…”
Section: Importancementioning
confidence: 99%
“…Essential acute asthma interventions performed by EMS may include support of oxygenation and ventilation and administration of inhaled or intravenous medications. The role of EMS in the care of children with acute asthma has been examined in terms of demographics, treatments initiated, and impact on ED stays 7–9 . However, similar insights for adults are not known.…”
Section: Introductionmentioning
confidence: 99%